Amperometric Folic Acid Quantification Using a Supramolecular Tetraruthenated Nickel Porphyrin µ‐Peroxo‐Bridged Matrix Modified Electrode Associated to Batch Injection Analysis. Issue 10 (30th June 2015) - Ferreira, Luís M. C.; Martins, Paulo R.; Araki, Koiti; Toma, Henrique H.; Angnes, Lúcio
Abstract A supramolecular Nickel (II) porphyrin complex containing four pyridyl‐bis(2, 2′‐bipyridyl)chloro ruthenium meso substituents was submitted to successive voltammetric cycles in high alkaline media to produce a supramolecular matrix with Nickel centers linked by µ‐peroxo bridges, producing a highly stable thin film able to act as redox mediator for electrocatalytic oxidation of folic acid. The characterization of electrode surface material was performed by Scanning Electron Microscopy and Electrochemical Impedance Spectroscopy. The modified electrode was inserted into a batch injection electrochemical cell used for the rapid and precise quantification of folic acid in pharmaceutical products. The favorable hydrodynamic conditions provided by amperometry‐BIA association allowed a very high throughput with good linear range (1 to 200 µmol L−1) and low detection limit (7.37×10−7 mol L−1). The electrochemical method was applied to the quantification of folic acid in different tablet samples. The results were comparable with values indicated by the manufacturer and those found using high HPLC according to the Brazilian Pharmacopoeia; commercial samples were submitted to a procedure in order to remove lactose of tablets, since carbohydrates act as interfering species. This procedure together with the electrochemical method showed to be simple, rapid, efficient and an appropriate alternative for quantifying this compound in real samples.